Cementless Total Hip Replacement for the Management of Severe Developmental Dysplasia of the Hip in the Middle Eastern Population: A Prospective Analysis - Imam, Mohamed A.; Fathalla, Ismail; Holton, James; Nabil, Mohamed; Kashif, Fadhil (Frontiers in Surgery, 2016)
Introduction In the Middle East, severe developmental dysplasia of the hip (DDH) with subsequent high dislocation is often seen. We assessed the efficiency of total hip replacement (THR) with subtrochanteric shortening femoral osteotomy and trochanteric advancement in this population. Methods This prospective study assessed 25 female patients with symptomatic and severe (Crowe IV). Pre and post-operative Harris hip (HHS) and Oxford hip scores (OHS) were performed alongside assessment of leg length discrepancy (LLD) and the ability to sit in a cross legged position. Results The mean HHS and OHS improved preoperatively at one and ten years respectively (p-value˂ 0.001). The mean postoperative LLD was 3mm (0-8mm). Functionally, 22/25 patients were able to sit cross-legged. None of the 25 hips underwent revision during this period. Conclusion Total hip replacement with subtrochanteric shortening osteotomy in combination with trochanteric advancement is sufficient for the management of Crowe type IV hips in this population.